Law As a Marketing Gimmick—The Case of the German Corporate Governance Code - Lutz-Christian Wolff (Washington University Global Studies Law Review, 2004)
This Article first briefly explains the German corporate governance system in the context of global developments. This Article will then discuss the German Corporate Governance Code and related problems. Finally, this Article argues that the Code’s legislative goal is to promote Germany’s capital markets, while its normative impact is limited. The question is whether this new function of law as a marketing tool is justifiable.
Keywords: Corporate governance; Corporation law; Germany; International